OPTIMIZING EMPLOYEE SCHEDULING: IMPACTS ON PRODUCTIVITY, SATISFACTION, AND WORK- LIFE BALANCE IN THE HOTEL INDUSTRY (International Conference on Economics, Business, and Management Research (ICEBMR), 2026)
This qualitative study delves into the intricate relationship between employee scheduling practices and outcomes in the hotel industry, focusing on productivity, job satisfaction, and work-life balance. Guided by Social Exchange Theory, this paper combines primary and secondary data to unveil crucial insights through thematic analysis. The study highlights flexible scheduling positive impact, particularly through flextime, enabling employees to effectively balance personal and professional commitments, thereby enhancing commitment, productivity, and job satisfaction. Conversely, irregular schedules create dissatisfaction and work-family conflicts. Also, transparent communication, fair task distribution, and proactive management of unforeseen circumstances foster a positive social exchange dynamic between employees and organizations. It is recommended to implement clear flexible work policies, adopting workforce management software, fostering open communication channels, cross-training employees for versatile roles, offering fair rotating shifts, part-time/job-sharing opportunities, and conducting regular policy reviews. Despite some limitations in gathering data, this study offers valuable insights for policymakers, practical guidance for hotel management, and contributes to bridging the research gap in the literature, enriching the understanding of employee scheduling's impact in the hotel industry.
Keywords: Employee Scheduling; Productivity; Satisfaction; Work-Life Balance